2017
DOI: 10.1038/s41598-017-07811-7
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index, lipid accumulation product and intracranial atherosclerotic stenosis in middle-aged and elderly Chinese

Abstract: We investigated the association of the newly established lipid accumulation product (LAP) and visceral adiposity index (VAI) with intracranial atherosclerotic stenosis (ICAS) in middle-aged and elderly Chinese. From June 2012 to January 2013, consecutive patients ≥40 years of age who underwent cerebral vascular imaging for various medical reasons were enrolled in this study. Multivariate logistic regression models were used to evaluate the correlation of VAI and LAP with the risk of ICAS. In total, 845 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 43 publications
3
35
2
1
Order By: Relevance
“…This finding is in contrast to another study that reported that VAI was not superior to BMI in the assessment of CVD event risk in women . The VAI has also been found to be associated with subclinical coronary atherosclerosis, as measured by the coronary artery calcium score, and with intracranial atherosclerotic stenosis in middle‐aged and elderly Chinese women . In a study conducted in China with people aged over 40 years, VAI was associated with arterial stiffness, measured through brachial‐ankle pulse wave velocity, which was not observed for WC alone .…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This finding is in contrast to another study that reported that VAI was not superior to BMI in the assessment of CVD event risk in women . The VAI has also been found to be associated with subclinical coronary atherosclerosis, as measured by the coronary artery calcium score, and with intracranial atherosclerotic stenosis in middle‐aged and elderly Chinese women . In a study conducted in China with people aged over 40 years, VAI was associated with arterial stiffness, measured through brachial‐ankle pulse wave velocity, which was not observed for WC alone .…”
Section: Discussioncontrasting
confidence: 97%
“…P < 0.05: a. NGT vs prediabetes, b. NGT vs DM, c. Prediabetes vs DM atherosclerotic stenosis in middle-aged and elderly Chinese women. 19 In a study conducted in China with people aged over 40 years, VAI was associated with arterial stiffness, measured through brachial-ankle pulse wave velocity, which was not observed for WC alone. 20 In our study, we revealed a borderline insignificant association between VAI and cIMT across the VAI tertiles, while such a relationship was not found between BMI or WC and cIMT.…”
Section: Discussionmentioning
confidence: 94%
“…risk of intracranial atherosclerotic stenosis in middle-aged and elderly Chinese females [27], whilst it may be a valuable index in predicting the risk of hypertension in the Chinese population [28]. Moreover, in a cross-sectional study with 191 adults and elderly participants LAP exhibited high accuracy in visceral obesity discrimination, as assessed by the area of visceral adipose tissue identified by computed tomography [29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[8] Nevertheless, previous studies have shown that VAI is more in uential in females. [13,17,18] We, therefore, conducted a strati ed multivariable analysis by sex to con rm these results. All variables with P < 0.05 were considered signi cant in this study.…”
Section: Discussionmentioning
confidence: 88%
“…[8] This visceral adiposity index (VAI) was closely associated with metabolic disease, cardiovascular disease, and even atherosclerosis. [10][11][12][13][14] However, studies on cerebrovascular disease is still lacking. Silent brain infarct (SBI) is a subclinical pathological condition that is commonly found in elderly individuals.…”
Section: Introductionmentioning
confidence: 99%